Clinical and Biochemical Characteristics of Acute Pancreatitis Patients Attended in a Tertiary Hospital of Bangladesh - Shaifuddin, Syed Mohammad; Sarker, Jaida Jalal (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Acute pancreatitis is a complex, life- threatening disease resulting from acute inflammation of the pancreas which causes considerable morbidity and mortality among the patients. Objectives: To find out the clinical and biochemical characteristics of acute pancreatitis patient attended at the Combined Military Hospital (CMH) Dhaka. Methods: This observational study was conducted at CMH Dhaka among 40 patients of acute pancreatitis admitted from 1st January 2013 to 30th June 2013. Data were collected through face-to-face interview using a pre-tested semi- structured questionnaire and review of the hospital records. Results: Highest number of the respondents (42.5%) belongs to the age group of 20-39 years. The mean age was 44.90 years (±13.46) years and 60.0% of them were male. More than half (57.5%) of the respondents had monthly income in the 20001 to 50000 Taka with average of 31,650(±15,255.60) Taka. All the patients presented with pain in the abdomen which was followed by nausea/ vomiting (82.5%), abdominal distention (72.5%). On examination, it was revealed that all the respondents had abdominal tenderness which was followed by muscle guard (10.0%), ascites (7.5%) and jaundice (5.0%). Almost half (47.50%) of the respondents developed acute pancreatitis due to stone in the gall bladder which was followed by idiopathic origin (30.0%). Eighty five percent of the patients had severe symptoms and rest (15%) had mild symptoms. All the respondents had elevated serum amylase level and 82.5% had elevated serum lipase level. Conclusion: Acute pancreatitis mostly affect young adult male. Most common clinical presentations are upper abdominal pain, nausea/vomiting and abdominal tenderness. Gallstone is the commonest cause of the condition. Serum amylase is the most important biochemical abnormality found in acute pancreatitis. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 38-41